The Sustainability of Public Finances in Republic of Moldova Under EU Fiscal Rules - Covalschi Tatiana; Lazăr Sebastian (Scientific Annals of Economics and Business, 2016)
This paper analyses public finances sustainability in the Republic of Moldova under the European Union fiscal rules, by estimating the structural budget balance indicator using a three steps methodology. We concluded that, except for 2009, the Republic of Moldova complies with the Maastricht numerical fiscal rule; however it does not comply with the new fiscal rules regarding the structural deficit and public expenditures growth that had been set by the Fiscal Compact. The fact that budget deficits and public debt had been sustainable was mainly because of the concessions made by the external creditors in restructuring the public debt and was not a merit of national government. Moreover, since the regular budget deficit and the structural one tell different stories, we strongly advocate for using the latter in order to complement the existing data with a medium-term budgetary view.